New Parameter for In-Office Dental Bleaching - Presoto, Cristina Dupim [UNESP]; Bortolatto, Janaina Freitas [UNESP]; Carvalho, Priscila Petrucelli Freire De [UNESP]; Trevisan, Tamara Carolina [UNESP]; Floros, Michael Christopher; Junior, Osmir Batista De Oliveira [UNESP] (Hindawi, 2016)
Dental bleaching is considered a conservative and biologically safe treatment for discolored teeth. Despite this, one of the major undesirable effects of bleaching is dentin sensitivity which may occur during and after treatment. To address these sensitivity issues, new dental bleaching preparations with lower concentrations of hydrogen peroxide (H2O2) have recently been introduced to the market. This paper presents a clinical case report of a 20-year-old female patient admitted to the Araraquara Dental School, UNESP, Brazil. The patient underwent dental bleaching using one of the new products with reduced hydrogen peroxide concentration, Lase Peroxide Lite 6%, a 6% H2O2 gel containing titanium oxide nanoparticles doped with nitrogen (6% H2O2/N-doped TiO2).